2015
DOI: 10.5032/jae.2015.04059
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Strategic Message Selection on Residents' Intent to Conserve Water in the Landscape

Abstract: Changing individuals' behaviors is a critical challenge for Extension professionals who encourage good irrigation practices and technologies for landscape water conservation. Multiple messages were used to influence two predictors of behavioral intent informed by the theory of planned behavior, Florida residents' (N = 1,063) attitude and perceived behavioral control. Individuals were randomly assigned to one of four treatment groups, each receiving a different strategically framed message. This article contrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
33
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 46 publications
0
33
0
Order By: Relevance
“…Data collected for this study were part of a multi-year project exploring water conservation behaviors of Florida residents over a period from 2014 to 2016. As there is no existing sampling frame of our target population (Warner et al, 2015;Warner, Kumar Chaudhary, et al, 2017), Florida residents with irrigated lawns/landscapes, we used a professional survey sampling company to secure a purposive sample using an online opt-in panel, which is considered appropriate for understanding an audience when random sampling is not possible (Baker et al, 2013;Bryman, 2008). We used a researcher-developed electronic survey instrument to collect data during the three-year period.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Data collected for this study were part of a multi-year project exploring water conservation behaviors of Florida residents over a period from 2014 to 2016. As there is no existing sampling frame of our target population (Warner et al, 2015;Warner, Kumar Chaudhary, et al, 2017), Florida residents with irrigated lawns/landscapes, we used a professional survey sampling company to secure a purposive sample using an online opt-in panel, which is considered appropriate for understanding an audience when random sampling is not possible (Baker et al, 2013;Bryman, 2008). We used a researcher-developed electronic survey instrument to collect data during the three-year period.…”
Section: Methodsmentioning
confidence: 99%
“…A study conducted by the NRDC (2010) found that more than As a policy tool, education plays an important role in raising environmental awareness and promoting conservation behaviors to ensure future water security. Since the majority of household water can be used for landscape irrigation, organizations such as Extension are focusing on influencing residential landscape practices through education to promote water conservation (St. Hilaire et al, 2008;Warner, Rumble, Martin, Lamm, & Cantrell, 2015;. In Florida, Extension promotes residential landscape water conservation through practices such as low-volume irrigation and precise irrigation scheduling techniques (University of Florida / Institute of Food and Agricultural Sciences Extension, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In order to avoid future water conflicts, water concerns need to be understood and recognized by all interest groups including the general public and decision makers (Warner, Rumble, Martin, Lamm, & Cantrell, 2015;Young & Dhanda, 2013). These groups must understand one another and work together if society wants to develop and implement sustainable solutions to the widespread water problems that are increasing over time (Huang & Lamm, 2015a;Odera et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Gorham et al (2014) identified how critical thinking style or the way individual's think about and seek out information had a moderate relationship with water conservation intentions. Similarly, the role of salient and tailored messages to encourage water conservation behaviors has provided evidence that such messaging can encourage individuals to participate in environmentally responsible behavior (Warner, Rumble, Martin, Lamm, & Cantrell, 2015). When making information salient for consumers to participate in behaviors, or frame a message, communicators select aspects of information "to promote a particular problem, definition, casual interpretation, moral evaluation, and/or treatment recommendation" (Entman, 1993, p. 52).…”
mentioning
confidence: 99%